Pichia kudriavzevii em altas concentrações de furfural, hidroximetilfurfural e fenol é eficiente para a produção de etanol 2G - Natale, Katia Gabriela de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
During the pre-treatment of the lignocellulosic biomass to produce second generation ethanol substances that inhibit the fermentation process can be generated. The detoxification of the hydrolysate is recommended to remove the inhibitors. However, it is an onerous process. Thus, it is necessary to use microorganisms that are resistant to the toxic compounds. The purpose of this work was to study how different concentrations of the inhibitors furfural, hydroxymethylfurfural and phenic acid (phenol) can affect the ethanol production by Pichia kudriavzevii LJ03. The experimental design was completely randomized, evaluating the dosages of 0.2 g.L-1; 0.5 g.L-1; 1.0 g.L-1; 1.5 g.L-1 and 2.0 g.L-1 for each inhibitor. The results showed that cell viability in the presence of hydroxymethylfurfural (93.68%) was higher than in those treatments with furfural (44.87%), and phenic acid (67.95%). The yeast produced high concentrations of ethanol at all dosages of hydroxymethylfurfural. While in the presence of furfural and phenic acid the production occurred up to 0.5 g.L-1 and 1.0 g.L-1, respectively. Therefore, this research demonstrated the ability of P. kudriavzevii LJ03 to continue producing second generation ethanol in synthetic medium without detoxification.

Durante o pré-tratamento da biomassa lignocelulósica para produzir etanol de segunda geração pode haver a formação de substâncias que inibem o processo fermentativo. A destoxificação do hidrolisado visa remover os inibidores; porém é um procedimento oneroso. Assim, faz-se necessário o uso de microrganismos resistentes aos compostos tóxicos. O presente trabalho objetivou estudar como diferentes dosagens dos inibidores furfural, hidroximetilfurfural e ácido fênico (fenol) afetam a produção de etanol por Pichia kudriavzevii LJ03. O delineamento experimental foi inteiramente casualizado, avaliando-se as doses de 0,2 g.L-1; 0,5 g.L-1; 1,0 g.L-1; 1,5 g.L-1 e 2,0 g.L-1 para cada inibidor. Os resultados mostraram que a viabilidade celular média na presença de hidroximetilfurfural (93,68%) foi superior aos tratamentos com furfural (44,87%) e ácido fênico (67,95%). A levedura produziu elevadas concentrações de etanol em todas as doses de hidroximetilfurfural. Enquanto na presença de furfural e ácido fênico a produção ocorreu até 0,5 g.L-1 e 1,0 g.L-1, respectivamente. Portanto, esta pesquisa demonstrou a capacidade de P. kudriavzevii LJ03 de permanecer produzindo etanol de segunda geração em mosto sintético sem destoxificação.
Pichia kudriavzevii at high concentrations of furfural, hydroxymethylfurfural and phenol is efficient for 2G ethanol production
Keywords: Microbiologia; Biocombustíveis; Biomassa; Fermentação; Inibidores